Pengaruh Return On Asset dan Debt To Equity Ratio Terhadap Nilai Perusahaan PT Bank ABC Pada Bulan Januari-Desember 2023 - Siska Nurchofifa; Diah Nur Hayati; M. Dadung Bimantoro; Shonya Putri Asalisa; Fitriya Andriyani (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
ROA is a ratio that measures a company’s ability to generate profits from its assets, while DER is a ratio that measures the proportion of debt to equity in the company’s capital structure. The research method used is multiple linear regression analysis, which allows the researcher to examine the relationship between two independent variables (ROA and DER) and the dependent variable (firm value). The results of the study indicate that ROA has a positive and significant effect on firm value, suggesting that increased efficiency in asset utilization will enhance firm value. Conversely, DER has a negative effect, indicating that an increased proportion of debt to equity can reduce firm value. The conclusion of this study is that to enhance firm value, PT Bank ABC needs to focus on improving the efficiency of asset utilization and better manage its capital structure to reduce dependence on debt.